Pulping Studies of Agathis robusta - Guha, S. R. D.; Singh, Man Mohan; Bhola, P. P.; Chittivanich, Boon Sueb; Gay, Lee Seng (Indian Forester, 1970)
With the increase of standard of living in the country it is essential to produce different grades of pulps and papers for domestic consumption. To meet the production target, it is essential to produce more of fibrous raw materials especially long-fibre material. Agathis robusta is a fast-growing exotic conifer from Australia. Wrapping papers, writing and printing papers and rayon grade pulps have heen produced on the laboratory scale with encouraging results. Proximate chemical analysis of wood as well as of fibre dimensions and their distribution in the pulp have also been recorded. It is seen that this material is suitable for producing the various grades of pulps and papers enumerated above.